Synthesis and Characterization of Transition Metals Ions Complexes with 2-Thioxoimidazolidin-4-One Schiff Base as Ligand - Al-Bayati, Sinan Midhat; Rasheed, Anaam Majeed; Mohammed, Enas Zuhair; Hassan, Zeina Kudair; Chali, Amjad; Hussein, Amal Mohammed (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
Mn(II), Co(II), Ni(II), Cu(II), and Cr(III) metal complexes with the ligand (L) [3-(2nitro benzylidene) amino-2-thioxoimidazolidin-4-one] have been prepared and characterized in their solid state using the elemental micro analysis (C.H.N.S), flame atomic absorption, UV-Vis spectroscopy, FT-IR, magnetic susceptibility measurements, and electrical molar conductivity. The ratio of metal to ligand [M:L] was got for all complexes in the ethanol by using the molar ratio method, which produced comparable results with those results obtained for the solid complexes. From the data of all techniques, octahedral geometry was proposed for Cr(III), Mn(II), and Co(II) complexes, while tetrahedral structure was proposed for Ni(II), Cu(II) complexes.